A Study on Hydrodynamic Behavior of Fine Sediment in Retention Structure Using Particle Image Velocimetry. (1st December 2016) - MoayeriKashani, Masoumeh; Hin, Lai Sai; Ibrahim, Shaliza; Sulaiman, Nik Meriam, Nik
ABSTRACT: : Detention ponds are one type of stormwater best management practices (BMPs) that can be used for the quantity control of stormwater. The pond works by reducing peak discharge downstream through temporary storage and gradual release. In this paper, a new experimental procedure using particle image velocimetry (PIV) is introduced for a two‐dimensional study of the hydrodynamic behavior of fine particles in a specially designed sediment basin. The hydrodynamic behavior of fine particles under different hydraulics parameters was achieved by shifting outlet placement, using different particle‐size diameters, varying the distance of the inlet from the water surface, and varying the flow rate. The same inlet and outlet level reduced fine‐particle dispersion and a lower flow rate assisted with controlling high siltation. Furthermore, smaller spherical particles had more influence on fine particle suspension. Therefore, controlling the hydraulic parameters can decrease the siltation problem level.